Control strategy of electrolyzer in a wind-hydrogen system considering the constraints of switching times. (27th September 2019) - Fang, Ruiming; Liang, Yin
Abstract: In order to improve the operational performance of alkaline electrolyzers powered by wind power, the influences of the fluctuating wind power on alkaline electrolyzers must be taken in accounts. In pursuing this goal, the influences of fluctuating wind power on both the hydrogen production and the self-safety of alkaline electrolyzer is discussed firstly. And a wind-hydrogen integrated energy system (WHIES) integrated supercapacitor is designed to smooth the fluctuation of wind power. In which, the fluctuation of wind power is divided into two kinds, instantaneous fluctuation and wide power fluctuation, the former is absorbed by supercapacitors, the latter is overcomed by adopting a modular adaptive control strategy to optimize the operation mode of alkaline electrolyzer. A simulation has been developed for a specific wind farm located in Northeast China. The simulation results show that under the condition of fluctuating wind power, the WHIES with the proposed control strategy can reduce the switching times of electrolyzers by 93.5% and increase hydrogen production by more than 44.18% when compared with other control strategies. Highlights: Discussion the influence of the fluctuating wind power on alkaline electrolyzer. A WHS Model can smooth the fluctuation wind power on hydrogen production. Smoothing the instantaneous fluctuation of wind power by using supercapacitors. A modular adaptive strategy to control the switching of electrolyzer. Model validation through comparison with different strategies.